A trial engagement? Innovative free and other service trials. Issue 1 (12th February 2018) - Bednall, David H.B.; Oppewal, Harmen; Laochumnanvanit, Krongjit; Nguyen, Cuc
Abstract : Purpose: This paper aims to discover how consumers process an innovative set of systematically varied service trial offers and how this affects their learning and interaction as precursors to customer engagement. Design/methodology/approach: The research uses experiments that manipulate pricing, type of service and delivery method. A repeated-measures design was used with a sample of 396 participants. Findings: Free (as opposed to cost or full price) service trials were more likely to be accepted, with perceived truthfulness of the trial offer and perceived obligation mediating the relationship. Credence service trials generate higher levels of perceived obligation than experience service trial offers, while personal services are more likely to lead to trial adoption. Research limitations/implications: The research can be extended to well-recognized brands and further mixed service contexts. Practical implications: Trial offers of new services are best targeted at buyers who are in the likely buyer group. The trial offer may accelerate time to purchase and relieve perceived risks. The trials of credence services need further signals of quality in the trial itself for consumers to adopt the full service. With personal service trials, skeptical consumers need assurance as to what will happen after the trial experience. Free trials may actually devalue a service, threatening engagement. Originality/value: Uniquely, service trial offers are systematically manipulated using experience versus credence and personal versus impersonal trials to determine their effect on acceptance of the trial offer and the full service. Additionally, the study compares free, cost price and full price trial offers.